Nanophotonic Information Physics Nanointelligence and Nanophotonic Computing - Naruse, Makoto; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book provides a new direction in the field of nano-optics and nanophotonics from information and computing-related sciences and technology. Entitled by "Information Physics and Computing in NanosScale Photonics and Materials(3y(B, IPCN in short, the book aims to bring together recent progresses in the intersection of nano-scale photonics, information, and enabling technologies. The topic will include (1) an overview of information physics in nanophotonics, (2) DNA self-assembled nanophotonic systems, (3) Functional molecular sensing, (4) Smart fold computing, an architecture for nanophotonics, (5) semiconductor nanowire and its photonic applications, (6) single photoelectron manipulation in imaging sensors, (6) hierarchical nanophotonic systems, (8) photonic neuromorphic computing, and (9) SAT solver and decision making based on nanophotonics.s
Information Physics in Nanophotonics -- DNA Self-assembled Nanostructures for Resonance Energy Transfer Circuits -- Functional Molecular Sensing Using Photonic DNA Nanoprocessor -- Smart Fold Computing - A Distributed Approach to Overcome Diffraction Limit of Light -- Nonlinear Behaviors in III-V Semiconductor Nanowires and Their Application to Information Detection and Processing -- Single Photoelectron Manipulation and Detection with Sub-nanosecond Resolution in CMOS Imagers -- Engineering of Nanometric Optical System Based on Optical Near-field Interactions for Macroscale Applications -- Photonic Neuromorphic Signal Processing and Computing -- Quantum Dot-based SAT Solver and Decision Maker.
Keywords: Physics; Engineering; Nanotechnology; Physics; Optics and Electrodynamics; Nanotechnology and Microengineering; Information Systems Applications (incl. Internet).; Nanotechnology; Nanoscale Science and Technology